Dynamic effects of monetary policy shocks on macroeconomic volatility - Haroon Mumtaz; Konstantinos Theodoridis (Cardiff University, Cardiff Business School, 2018)
We develop a VAR that allows the estimation of the impact of monetary policy shocks on volatility. Estimates for the US suggest that an increase in the policy rate by 1% is associated with a rise in unemployment and inflation volatility of about 15%. Using a New Keynesian model, with search and matching labour frictions and Epstein-Zin preferences we show that these volatility effects are driven by the coexistence of agents' fears of unemployment and concerns about the (in) ability of the monetary authority to reverse deviations from the policy rule with the impact magnified by the agents' preferences.
Keywords: E30; E40; E52; C11; C13; C15; C50; 330; DSGE; Non-Linear SVAR; New Keynesian; Search and Matching Frictions; Epstein-Zin preferences; Stochastic Volatility